2020
DOI: 10.3390/biom10040625
|View full text |Cite
|
Sign up to set email alerts
|

Association of microRNA Expression and BRAFV600E Mutation with Recurrence of Thyroid Cancer

Abstract: Many miRNAs and cancer-related mutations have been proposed as promising molecular markers of papillary thyroid carcinoma (PTC). However, there are limited data on the correlation between miRNA expression, BRAFV600E mutation, and PTC recurrence. Therefore, to evaluate the potential of BRAFV600E mutation and five selected miRNAs (-146b, -222, -21, -221, -181b) in predicting PTC recurrence, these molecular markers were analyzed in 400 formalin-fixed, paraffin-embedded PTC tissue specimens. The expression levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 53 publications
(101 reference statements)
3
25
2
Order By: Relevance
“…Previous studies have demonstrated that miR-146b, miR-221 and miR-222 are the most consistently overexpressed miRNAs in PTC tissue [ 14 , 22 , 45 , 46 ]. Moreover, studies that explored miR-146b, miR-222 and miR-221 expression in plasma samples showed their consistent upregulation in PTC compared to the HC group [ 22 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that miR-146b, miR-221 and miR-222 are the most consistently overexpressed miRNAs in PTC tissue [ 14 , 22 , 45 , 46 ]. Moreover, studies that explored miR-146b, miR-222 and miR-221 expression in plasma samples showed their consistent upregulation in PTC compared to the HC group [ 22 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is already known that miR-146b, miR-21, miR-221, miR-222, miR-181b are dysregulated in PTC. These molecules showed potential as biomarkers in PTC tissue and plasma/serum studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. It was also demonstrated that downregulation of miR-181b inhibits proliferation and promotes apoptosis in thyroid cancer TPC1 cells, making this miRNA a possible target for PTC treatment [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results using HR confirmed that the BRAF V600E mutation is not associated with recurrence. Recent studies have indicated that the effect of the BRAF V600E mutation for PTC recurrence would be minimized, or even be protective, after adjustment of possible confounders including age, sex, tumor size, and multifocality [21,26,28]. Pamedytete et al reported that the adjusted HR of the BRAF V600E mutation was 0.80 (95% CI 0.47-1.36), although the unadjusted HR was 1.01 (95% CI 0.62-1.64) for the recurrence of PTC [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that the effect of the BRAF V600E mutation for PTC recurrence would be minimized, or even be protective, after adjustment of possible confounders including age, sex, tumor size, and multifocality [21,26,28]. Pamedytete et al reported that the adjusted HR of the BRAF V600E mutation was 0.80 (95% CI 0.47-1.36), although the unadjusted HR was 1.01 (95% CI 0.62-1.64) for the recurrence of PTC [21]. In the present meta-analysis, the pooled HR of the enrolled studies also decreased from 1.30 (95% CI 0.91-1.85) to 1.16 (95% CI 0.78-1.71) after adjustment, which is consistent with the previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation